DEPOSITIONAL FACIES AND RADIOCARBON AGES FROM DTl CORE IN THE MEKONG RIVER DELTA: EVIDENCE OF INCISED- VALLEY FILLING IN HOLOCENE TRANSGRESSION - Lap, Nguyen Van; Oanh, Ta Thi Kim (Vietnam Journal of Marine Science and Technology, 2008)
The  DTJ  boring site located in  Dong Thap province, 51.5m  in depth, gives a good opportunity to  study Holocene  depositional facies  related to  sea- level changes at an incised valley  of the  Mekong  River. Based on  lithological units  and radiocarbon dating,  six depositional facies  are  recognized in  asending  order  as follows:  marsh/tidal flat sandy silt, sub- to  intertidal flat  sandy silt,  inner  bay/prodelta  mud,  delta  ji-ont  sandy  silt,  sub- to intertidal flat  sandy  silt  and flood plain  silty  clay facies.  A  34. 5m  thick- succession from marsh/tidal flat sandy silt facies  to inner  bay/prodelta mudfacies  suggests  sea- level rising Moreover, this succession was dated 11,285 to  7, 090 ca.y.BP, and its accumulation rates are high at 4.80- 1 6.20mmy  l  These  data  suggest that a high sediment supply from  the  Mekong River accumulated at the incised valley throughout early to middle Holocene transgression.